Sensibilidade de Hemileia vastatrix a estrobilurinas e metodologia para avaliar germinação de esporos em microplacas de “Elisa” - Bartelega, Viviane (2022)
Rust, caused by Hemileia vastatrix, a biotrophic fungus, is considered the most devastating disease of coffee. Among the disease control measures, there is the use of fungicides. Among them, those of the chemical group of strobilurins. Although there is still little information about the change in H. vastatrix sensitivity to these products, there are records for other pathosystems. However, in vitro studies for optimal dose response selection and fungicide sensitivity analysis are still laborious and material consuming. Therefore, this work was carried out with the objectives of developing the methodology to carry out germination tests of Hemileia vastatrix spores in 'Elisa' microplates and to identify the sensitivity of Hemileia vastatrix to strobilurins in vitro. In addition, in the field, the main fungicides of this chemical group were evaluated in comparison with multisite and mixture with triazoles. The methodology was feasibility, with the best concentrations of spore suspension being 103 or 104 and the best amounts to be deposited on the plate are from 150 to 250 microliters, with 45% germination. The highest germination temperatures were 23oC combined with 18 or 24 hours of incubation and 25oC combined with 10, 18 or 24 hours of incubation, with germination higher than 50%. In in vitro tests for sensitivity to strobilurins, the populations of Hemileia vastatrix tested were sensitive to azoxystrobin, pyraclostrobin and picoxystrobin. However, there was a difference in the levels of sensitivity between the isolates. A dose of 128 ppm or mg/kg of active ingredient can be used as a dose response for testing the sensitivity of Hemileia vastatrix to strobilurins. In the controlled environment, under greenhouse conditions and in the field, differences in sensitivity were not observed, using the field dose of strobilurins (p<0.05). In the second year evaluated, in the field, picoxystrobin, pyraclostrobin and the mixture of the latter with epoxiconazole obtained increase in the productivity in relation to the other treatments (p<0.05).